PAHs in decaying Quercus ilex leaf litter: Mutual effects on litter decomposition and PAH dynamics (Chemosphere, 2014)
The investigation of the relationships between litter decomposition and polycyclic aromatic hydrocarbons (PAHs) is important to shed light not only on the effects of these pollutants on fundamental ecosystem processes, such as litter decomposition, but also on the degradation of these pollutants by soil microbial community. This allows to understand the effect of atmospheric PAH contamination on soil PAH content via litterfall. At this aim, we studied mass and PAH dynamics of Quercus ilex leaf litters collected from urban, industrial and remote sites, incubated in mesocosms under controlled conditions for 361d. The results highlighted a litter decomposition rate of leaves sampled in urban>industrial>remote sites; the faster decomposition of litter of the urban site is also related to the low C/N ratio of the leaves. The PAHs showed concentrations at the beginning of the incubation of 887, 650 and 143ngg−1d.w., respectively in leaf litters from urban, industrial and remote sites. The PAHs in litter decreased along the time, with the same trend observed for mass litter, showing the highest decrease at 361d for the urban leaf litter. Anyway, PAH dynamics in all the litters exhibited two phases of loss, separated by a PAH increase observed at 246d and mainly linked to benzo[e]pyrene.

Polycyclic aromatic hydrocarbon contamination in an urban area assessed by Quercus ilex leaves and soil (Environmental Science and Pollution Research, 2014)
We investigated the PAH contamination of Naples urban area, densely populated and with high traffic flow, by analyses of environmental matrices: soil and Quercus ilex leaves. Being some PAHs demonstrated to have hazardous effects on human health, the accumulation of carcinogenic and toxic PAHs (expressed as B(a)Peq) was evaluated in the leaves and soil. The main sources of the PAHs were discrim- inated by the diagnostic ratios in the two matrices. The urban area appeared heavily contaminated by PAHs, showing in soil and leaves total PAH concentrations also fivefold higher than those from the remote area. The soil mainly accumulated heavy PAHs, whereas leaves the lightest ones.Median values of carcinogenic PAH concentrations were higher in soil (440 ng g−1 d.w.) and leaves (340 ng g−1 d.w.) fromthe urban than the remote area (60 and 70 ng g−1 d.w., respectively, for soil and leaves). Also, median B(a)Peq concentrations were higher both in soil and leaves from the urban (137 and 63 ng g−1 d.w., respectively) than those from the remote area (19 and 49 ng g−1 d.w., respectively).Different from the soils, the diagnostic ratios found for the leaves discerned PAH sources in the remote and urban areas, highlighting a great contribution of vehicular traffic emission as main PAHsource in the urban area. Responsible

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.

Long-term PAH accumulation after bud break in L. leaves in a polluted environment (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site

Long-term PAH accumulation after bud break in L. leaves in a polluted environment - Alfani, a; Nicola, F.; Maisto, G.; Prati, M. (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site
Keywords: air contamination; carcinogenic pahs; pah dynamics; pah leaf accumulation; polycyclic aromatic hydrocarbons

Assessment of nutritional status and trace element contamination of holm oak woodlands through analyses of leaves and surrounding soils. (The Science of the total environment, 2003)
The nutritional status and trace element contamination of holm oak woodlands in Vesuvius National Park were assessed by analyses of Quercus ilex L. leaves and surrounding soils. The concentrations of Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, V and Zn were measured in 1-year-old leaves, and in the soils at 0-5 and 15-20 cm depths. The potentially available concentrations were also measured for the soils. The leaf element concentrations were similar to the Q. ilex chemical fingerprint, thus indicating a good nutritional status and the absence of short-term trace element depositions. Total K and V were more abundant in the deep soil layers than in the surface ones, whereas Cd and Pb showed higher values in the surface soils. This suggests that long-term soil accumulations of Cd and Pb are due to atmospheric input. The soil availabilities of Cd, Pb and Zn were high, and Cr availability was very low. A correlation between the available concentrations in the deep soil layers and leaf concentrations was found only for Zn.

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. - Alfani, a; Baldantoni, D.; Maisto, G.; Bartoli, G.; Virzo De Santo, A. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.
The following values have no corresponding Zotero field: accession-num: 15092919
Keywords: air pollution biomonitoring; leaf elemental analysis; no x; so 2; Trace Elements

Temporal and spatial variation in C, N, S and trace element contents in the leaves of Quercus ilex within the urban area of Naples. (Environmental pollution (Barking, Essex : 1987), 2000)
This paper presents a comparative analysis of the concentrations of C, N and S and several trace elements (Fe, Mn, Na, Zn, Cu, V, Pb, Ni, Cr, Cd) in leaves of Quercus ilex, an evergreen oak, collected in the urban area of Naples in 1989 and 1996. The samplings were carried out from 25 urban sites (roads with different traffic flows as well as urban and suburban parks) and from two remote areas as controls. Relative to 1989, the values measured in 1996 denote a strong decrement of S, Fe, Na, Pb, and Cr, with the exception of S in control sites. By contrast, C, N and Cd contents were higher in 1996 than in 1989. Cu and Ni showed a conspicuous increment in control sites as well as in urban sites facing the sea and in the parks, while in all the other urban sites these elements decreased remarkably. No significant difference was found in the leaf contents of Mn, Zn and V measured in 1989 relative to 1996. Both in 1989 and 1996 the contents of N, S, Fe, Na, Cu, Pb, V, Ni, Cr and Cd were significantly higher in leaves from urban sites than in the controls, reflecting the high degree of contamination of the urban area. Concentration factors expressed as the ratio of road/control values for most of the elements were still very high in leaves collected in 1996, though remarkably lower than in 1989.

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.